PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DALAM MENYELESAIKAN SOAL CERITA STATISTIK SISWA SMA NEGERI 9 BANDA ACEH - Fia Sufina Sadhore Jhd; Nur Ainun; Cut Nurul Fahmi; Rini Sulastri; Khairul Asri (Universitas Nias Raya, 2026)
The low problem-solving skills of students in mathematical word problems form the basis of this study, as their difficulties lie not only in understanding concepts but also in interpreting problems and selecting appropriate solution strategies. This condition highlights the need for an instructional model that helps students connect material to real-life situations, such as the Contextual Teaching and Learning (CTL) model. This study aims to examine the effect of the CTL model on improving students’ problem-solving skills in statistical word problems. Using a quantitative approach with a one-group pretest-posttest design, the study involved 20 students from class XI-B of SMA Negeri 9 Banda Aceh as the sample. Data were collected through a 3-item essay test given in the pretest and posttest, and analyzed using normality test, homogeneity test, paired sample t-test, and N-gain test. The results showed an increase in the average score from 33.10 in the pretest to 55.10 in the posttest, with the paired sample t-test yielding a significance value of 0.000 < 0.05. Based on these findings, the alternative hypothesis is accepted, indicating that the Contextual Teaching and Learning model significantly improves students’ problem-solving skills in statistical word problems.